Declining Abundance of Coccinellidae (Coleoptera) Among Crop and Prairie Habitats of Eastern South Dakota, USA - Hesler, Louis S.; Beckendorf, Eric A. (Frontiers in Conservation Science, 2021)
Lady (= ladybird) beetles (Coleoptera: Coccinellidae) provide agroecosystem services as major predators of aphids and other pests of field crops. Several native coccinellids in North America have declined in association with the introduction of invasive species of lady beetles. In particular, populations of three native species declined drastically (Coccinella transversoguttata richardsoni) or effectively disappeared (Coccinella novemnotata, Adalia bipunctata) from agricultural landscapes in eastern South Dakota, U.S.A., following establishment of an invasive coccinellid (Coccinella septempunctata) in the 1980s. Since then, two other nonnative coccinellids (Harmonia axyridis, Hippodamia variegata) have established in eastern South Dakota, but long-term analysis of their impact on the aphidophagous coccinellid guild is lacking. This paper summarizes long-term results from 14 years (2007-2020) of sampling coccinellids by sweepnet and timed searches in five field crops and restored prairie in eastern South Dakota. In all, 17,348 aphidophagous coccinellids comprising 10 species were sampled. Two invasive species (Coc. septempunctata, Har. axyridis) were the third- and fourth-most abundant species, respectively. The seven most abundant species constituted 99% of all coccinellids sampled and were recorded from all six habitats. However, coccinellid species ranged considerably in their evenness of habitat use, resulting in differences in rank abundance among habitats. Coccinellid assemblages were similar for alfalfa and winter wheat, but not for other habitats, which possessed distinct coccinellid assemblages based on rank abundance. Annual abundance of coccinellids varied considerably within habitats, but declining trends were evident from significant negative regressions in annual abundance for adult and immature coccinellids in corn and adults in soybean. As a group, native adult coccinellids showed a significant declining trend in corn but not in other habitats, whereas trends for nonnative adult coccinellids were non-significant in all habitats. Sample rates of coccinellids in alfalfa, spring grains, and corn in this study were 74%, 26% and 6%, respectively, compared to that of a previous study from the region, further indicating substantial decreases in coccinellid abundance. Possible explanations and implications for observed patterns in coccinellid diversity and individual species abundances in field crops and restored prairie of eastern South Dakota are discussed with respect to prey, agronomic trends, and landscape factors.